Improving assessment of children with suspected respiratory tract infection in general practice - Cheng Chen; Ruth Crowley (BMJ Open Quality, 2019)
Upper respiratory tract infection (URTI) in children is one of the most common reasons for general practice (GP) attendance over the winter months. It is crucial to be able to risk stratify and determine the severity of illness in these patients. It is important both to recognise those who are clinically unwell and require treatment escalation, and also to not overprescribe antibiotics due to the ongoing problem of antibiotic overuse and resistance.This quality improvement project was undertaken to improve the way in which these consultations were held and also the way they were documented. It was recognised that key features in assessing a potentially unwell child were to measure their heart rate (HR) and respiratory rate (RR). As children can often deteriorate rapidly and their clinical course may not necessarily be easy to predict, we wanted to make sure that parents were being provided with safety netting information in the event that the child should become more unwell after the consultation.Through the course of our project, we managed to improve the proportion of consultations for URTI or ‘viral illness’ in children in which HR and RR were documented from 57% to 100%. The proportion of consultations in which safety netting information for parents was discussed and documented improved from 48% to 96%.By using quality improvement strategies, we have succeeded in improving both the safety and efficiency in the way children who present with URTI are assessed in GP.